2019
DOI: 10.1080/08880018.2019.1648619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multimodal exercise on clinical status and patient-reported outcomes in children undergoing hematopoietic stem cell transplantation

Abstract: There are limited data available regarding effectiveness of exercise training in children undergoing hematopoietic stem cell transplantation (HSCT). We aimed to investigate effects of multimodal exercise program on clinical status and patient-reported outcomes including pain, fatigue, depression, and quality of life (QOL) level of children and their parents' QOL level. Twenty-six children undergoing HSCT participated in this study. Clinical status, pain, fatigue, depression, and QOL level of children were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 26 publications
(35 reference statements)
1
16
0
Order By: Relevance
“…The results of the seven studies included herein are explicitly indicated. The study results suggested that video game intervention (Kurt & Savaşer, 2013) positively affected the quality of life of adolescents with cancer and that the administration of a multimodal exercise programme reduced pain and increased the quality of life in children with cancer (Yildiz Kabak et al, 2019). Another article determined that informing the children with acute lymphoblastic leukaemia about chemotherapy increased their quality of life (Çetinkaya & Kurt, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the seven studies included herein are explicitly indicated. The study results suggested that video game intervention (Kurt & Savaşer, 2013) positively affected the quality of life of adolescents with cancer and that the administration of a multimodal exercise programme reduced pain and increased the quality of life in children with cancer (Yildiz Kabak et al, 2019). Another article determined that informing the children with acute lymphoblastic leukaemia about chemotherapy increased their quality of life (Çetinkaya & Kurt, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…All 21 studies reviewed reported that pediatric sibling donors express some form of psychosocial distress across the donation process. Only three studies in this review explicitly measured trauma symptoms experienced by donors and nondonors, which included anxiety (Erden et al, 2019;Packman et al, 1997a), depression (Erden et al, 2019;Packman et al, 1997a), and PTS symptoms (Gizli Coban et al, 2017;Packman et al, 1997a). However, within the remaining articles, siblings did express experiences of distress, fear, overwhelming pressure, guilt and blame, as well as emotional and social isolation.…”
Section: Discussionmentioning
confidence: 98%
“…The term "post-traumatic growth" was not explicitly used in the studies analyzed in this review; however, sibling donors described personal gains and growth post-donation in 48% of studies reviewed (D'Auria et al, 2015;Erden et al, 2019;Hoag et al, 2018;Hutt et al, 2015;MacLeod et al, 2003;Packman et al, 1997b;Pelletier et al, 2014;Pentz et al, 2014;Weiner et al, 2008;Wilkins and Woodgate, 2007), suggesting that a PTG lens was an appropriate fit. This novel analysis provides an increased understanding of the potential for growth during sibling donation, which may contribute to the development of new approaches to psychosocial intervention in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations